Boron carbide reinforced electrospun nanocomposite fiber mats for radiation shielding - Ozcan, Mucahid; Avcioglu, Suna; Kaya, Cengiz; Kaya, Figen (WILEY, 2023)
In this study, 1 wt% boron carbide (B4C) reinforced PVA nanofibers were fabricated by the electrospinning technique as a new generation of ultra-thin, lightweight, and flexible neutron shielding nanocomposites. The influence of B4C particles' size and morphology on the fiber formation and radiation shielding performance of fiber mats was investigated. The results indicate that the particle characteristics have a dramatic influence on the formation and properties of nanocomposites. The thicknesses of individual fibers reinforced with sol-gel synthesized nano-sized boron carbide particles were in the range of 50-250 nm, while those containing commercial B4C powder were produced in the thickness range of 1-2 mu m. In contrast to the commercial particles, the sol-gel synthesized nano B4C particles enhanced the fiber mat's density and the roundness of individual fibers. Both theoretical and experimental radiation shielding studies showed that B4C reinforcement successfully improved the neutron and gamma attenuation of the neat PVA matrix. Furthermore, it was found that a 6.5 mm thick PVA nanofiber mat, reinforced with only 1 wt% B4C nanoparticles shielded up to about 7.4% of the initial neutron flux. Compared to the neat PVA fiber mat, reinforcement of PVA fibers with 1 wt% sol-gel synthesized nano-sized boron carbide particles enhanced the neutron shielding by 50.31%. Moreover, even though B4C is not an effective gamma shielding reinforcement, the amplified density of nanocomposite fiber mats also enhanced gamma attenuation.
Keywords: electrospinning; fibers; nanocomposites; radiation; POLY(VINYL ALCOHOL); TEMPERATURE; COMPOSITES; PARTICLES; MEMBRANES; ALARA; Materials Science; Polymer Science